2007
DOI: 10.1016/j.jcf.2006.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Airway glucose concentrations and effect on growth of respiratory pathogens in cystic fibrosis

Abstract: BG> or =8 mmol L(-1) predicted elevated AG concentrations in CF, at least in nasal secretions. CFRD patients spent approximately 50% day with BG>airway threshold, implying persistently elevated AG concentrations. Further studies are required to determine whether elevated airway glucose concentrations contribute to accelerated pulmonary decline in CFRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
147
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(155 citation statements)
references
References 32 publications
(52 reference statements)
4
147
2
2
Order By: Relevance
“…Nutritional condition and pulmonary function begin to deteriorate several years prior CFRD diagnosis, a period in which minimal hyperglycemia is present (9,11). Modest increases in glycemia (≥ 144 mg/dL) may influence pulmonary function, as they promote a glycemic increase in the bronchial tree, which may facilitate the growth of respiratory pathogens (47). Fasting hyperglycemia (FH) does not appear to be relevant in the progression of the disease, as there was no difference in pulmonary function and nutritional condition among CFRD patients with and without FH (7).…”
Section: Pathophysiology Of Cfrdmentioning
confidence: 99%
“…Nutritional condition and pulmonary function begin to deteriorate several years prior CFRD diagnosis, a period in which minimal hyperglycemia is present (9,11). Modest increases in glycemia (≥ 144 mg/dL) may influence pulmonary function, as they promote a glycemic increase in the bronchial tree, which may facilitate the growth of respiratory pathogens (47). Fasting hyperglycemia (FH) does not appear to be relevant in the progression of the disease, as there was no difference in pulmonary function and nutritional condition among CFRD patients with and without FH (7).…”
Section: Pathophysiology Of Cfrdmentioning
confidence: 99%
“…Diabetes has been directly implicated in the pathophysiology of CF lung function decline, related to both the catabolic effect of insulin insufficiency on nutritional status and muscle mass (6)(7)(8)(9)(10) and the proinflammatory, proinfection impact of chronic hyperglycemia on lung function (11,12).…”
mentioning
confidence: 99%
“…In a study published in 2007, Brennan et al 133 compared BG and airway secretion glucose (using nasal secretions), but added studies of the growth rates of S. aureus and P. aeruginosa. They found that glucose was present in airway secretions in 85% of cases when BG levels were > 8 mmol/l, but in only 19% (but none with high airway glucose) when it was < 8 mmol/l.…”
mentioning
confidence: 99%